PSV-7 Colostrum Intake Level Is Related to Level of Total Circulating Proteins and Essential Amino Acids. (7th May 2021) - Suarez-Trujillo, Aridany; Senn, L Kirsten; Teeple, Kelsey; Shirley, Larissa K; McCabe, Conor; Mills, Kayla M; Klopp, Rebecca; Stewart, Kara R; Casey, Theresa
Abstract: Colostrum intake potentiates piglet survival by transfer of immune factors. Additionally, colostrum also contains nutritional and bioactive molecules which could promote piglet's growth and development. The objective of this study was to determine the effect of colostrum intake amount during the first 24h on plasma insulin, glucose, protein, and amino acid (AA) concentrations. Two female piglets were selected from 8 litters (n = 16) at birth and fed 10% (COL10) or 20% (COL20) colostrum based on birth weight over 12 bottle feedings occurring every 2h. Colostrum was collected from multiple sows and mixed to create a homogeneous pool. At birth and 24h, blood sample were collected, plasma separated and used to measure insulin, glucose, total protein, and AA concentrations. Analysis of the variance (PROC MIXED, SAS v.9.4) was used to evaluate significant (P≤0.05) differences between colostrum dose and time (birth vs. 24h). Colostrum intake did not influence plasma insulin at 24h (P=0.54). Glucose was higher at 24h (P< 0.001), but did not differ between COL10 and COL20 piglets (P=0.74). Total protein was greater at 24h (P< 0.001) as well as in COL20 compared to COL10 (P=0.006). Non-essential AAs (Ala, Asn, Asp, Cys, Gly and Glu) were reduced at 24h compared to birth (P< 0.03), while essential AAs (His, Ile, Met, Phe, Trp and Val) were increased after 24h of colostrum feeding (P< 0.05). At 24h, COL20 piglets had greater Ile and Met (P< 0.03) and tended (P=0.08) to have greater Leu and Phe. In conclusion, colostrum intake increases glycemia as well as total circulating proteins, and the dose of colostrum is related with greater circulation of total protein and essential AAs.